2018
DOI: 10.1080/19420862.2018.1496879
|View full text |Cite
|
Sign up to set email alerts
|

Platform development for expression and purification of stable isotope labeled monoclonal antibodies inEscherichia coli

Abstract: The widespread use of monoclonal antibodies (mAbs) as a platform for therapeutic drug development in the pharmaceutical industry has led to an increased interest in robust experimental approaches for assessment of mAb structure, stability and dynamics. The ability to enrich proteins with stable isotopes is a prerequisite for the in-depth application of many structural and biophysical methods, including nuclear magnetic resonance (NMR), small angle neutron scattering, neutron reflectometry, and quantitative mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 59 publications
(59 reference statements)
0
14
0
Order By: Relevance
“…Supporting the notion that the limiting factor is the correct assembly of LC and HC, higher molecular weights protein bands above 200 kDa were observed. Previous studies on expression and purification of IgG from SHuffle cells have observed similar mis-assembled IgG species that are mis-oxidized, as these high-molecular bands collapse into LC or HC, under reducing conditions (Leith et al 2019 ; Lobstein et al 2012 ; Reddy et al 2018 ). Binding capacity to Humira IgG’s cognate antigen TNFα was measured by ELISA and IgG concentration of the purified extracts were calculated (Fig.…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations
“…Supporting the notion that the limiting factor is the correct assembly of LC and HC, higher molecular weights protein bands above 200 kDa were observed. Previous studies on expression and purification of IgG from SHuffle cells have observed similar mis-assembled IgG species that are mis-oxidized, as these high-molecular bands collapse into LC or HC, under reducing conditions (Leith et al 2019 ; Lobstein et al 2012 ; Reddy et al 2018 ). Binding capacity to Humira IgG’s cognate antigen TNFα was measured by ELISA and IgG concentration of the purified extracts were calculated (Fig.…”
Section: Resultsmentioning
confidence: 85%
“…This was the case for the artificial PDI-GPx7 coupled redox pathway, engineered to improve IgG folding in SHuffle cells. Although great success was achieved in improving the folding of Humira IgG, little to no improvement was observed for two other IgG molecules tested, NIST mAb (Reddy et al 2018) and anti-MBP (Lobstein et al 2012) (data not shown). Many other IgG molecules and derivatives need to be evaluated under various expression conditions, to discern the specificity of the PDI-Gpx7 coupled disulfide bond formation in SHuffle cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SHuffle cells are the first example of how the Dsb system can be engineered for biotechnological applications. Using SHuffle cells, our group was able to express various antibody fragments and full-length antibodies in the cytoplasm (171), as well as isotopically labeled antibodies, by expressing them in minimal media (172). DsbB has also been engineered to improve protein production in the cytoplasm.…”
Section: Engineering E For Disulfide Bond Formationmentioning
confidence: 99%